Efficient and Stable Mesoscopic Perovskite Solar Cells Using a Dopant‐Free D–A Copolymer Hole‐Transporting Layer. Issue 4 (4th March 2021) - Tavakoli, Mohammad Mahdi; Po, Riccardo; Bianchi, Gabriele; Carbonera, Chiara; Kong, Jing
Abstract : Addressing the stability issue in perovskite solar cells (PSCs) is a crucial step for commercialization purposes. Finding a novel and stable hole‐transporting layer (HTL) is one of the most effective strategies to solve this problem. Herein, a new polymeric HTL, namely poly2, 7‐[(5, 5‐bis(3′, 7′‐dimethyloctyl)‐5 H‐1, 8‐dithia‐as‐indacenone]‐ alt ‐5, 5‐[5′, 6′‐bis(octyloxy)‐4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole] (PDTIDTBT) is synthesized, indicating a great hole‐transporting property as compared with the commonly used 2, 2′, 7, 7′‐tetrakis[N, N‐di(4‐methoxyphenyl)amino]‐9, 9′‐spirobifluorene (spiro‐OMeTAD) HTL. This polymer shows good mobility with suitable band alignment with respect to the triple A‐cation perovskite film, which is comparable with the state‐of‐art polymeric HTLs. Therefore, mesoscopic PSCs are fabricated by PDTIDTBT HTL and considered interface engineering technique using a thin layer of poly(methyl methacrylate) (PMMA) at the perovskite/HTL interface. Based on these modifications, a PSC with a maximum power conversion efficiency (PCE) of 19.89% is achieved, higher than the PCE of the spiro‐based PSC (19.28%). In addition, the PDTIDTBT‐based PSCs show excellent operational and ambient stability better than the spiro ones. Abstract : Herein, a new and dopant‐free polymeric hole‐transporting layer, i.e., poly2, 7‐[(5, 5‐bis(3′, 7′‐dimethyloctyl)‐5 H‐1, 8‐dithia‐as‐indacenone]‐ alt ‐5, 5‐[5′, 6′‐bis(octyloxy)‐4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole] (PDTIDTBT), for mesoscopic perovskite solar cells is synthesized and the efficiency and stability of the cells are improved as compared with spiro‐based devices.